2013
DOI: 10.1186/1869-5760-3-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of linseed oil to treat experimentally induced keratoconjunctivitis sicca in rabbits

Abstract: BackgroundThe objective of this study was to evaluate the effectiveness of various linseed oil (LO) preparations (oral, topical, oral and topical combined) in treating experimentally induced keratoconjunctivitis sicca (KCS) in rabbits. Twenty male New Zealand white rabbits were divided into four groups: group C (control), group OLO (oral LO), group TLO (topical LO), and group OTLO (oral and topical LO). The animals were evaluated weekly using Schirmer's tear test (STT), fluorescein test (FT), and Rose Bengal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 12 publications
0
15
1
3
Order By: Relevance
“…A recent study compared almond and linseed oil as diluents of tacrolimus, another immunosuppressor, in the treatment of KCS in rabbits and showed that linseed oil either as a diluent or in isolation was more effective than almond oil (16) . Another study evaluated the effectiveness of various linseed oil preparations (oral, topical, and an oral/topical combination) in treating experimentally induced KCS in rabbits, and concluded that orally or topically administered linseed oil was effective in the treatment of KCS, although the combined oral/topical treatment did not show additional benefits (15) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study compared almond and linseed oil as diluents of tacrolimus, another immunosuppressor, in the treatment of KCS in rabbits and showed that linseed oil either as a diluent or in isolation was more effective than almond oil (16) . Another study evaluated the effectiveness of various linseed oil preparations (oral, topical, and an oral/topical combination) in treating experimentally induced KCS in rabbits, and concluded that orally or topically administered linseed oil was effective in the treatment of KCS, although the combined oral/topical treatment did not show additional benefits (15) .…”
Section: Discussionmentioning
confidence: 99%
“…Linseed oil is given orally as an adjuvant therapy in patients with Sjögren's syn drome and KCS (13,14) . Some authors have reported the treatment of experimentally induced KCS in rabbits using linseed oil in various preparations (oral, topical, and oral/topical combination) (15,16) . In mice with experimentally induced KCS, the topical use of ω-3 and ω-6 has been shown to successfully control inflammatory symptoms (17) .…”
Section: Comparison Of 1% Cyclosporine Eye Drops In Olive Oil and In mentioning
confidence: 99%
See 1 more Smart Citation
“…O uso tópico da formulação oftálmica e do óleo de linhaça rico em ômega 3 e 6 melhorou os sintomas associados à CCS com redução significativa da ocorrência de hiperemia conjuntival, secreção ocular e opacidade corneal, o que está de acordo com os relatos sobre o tratamento da CCS com melhora dos sinais clínicos com a formulação oftálmica tópica em cães (Kirk, 1984;Severin, 1995;Pickett, 2001;Andrade, 2008) e do uso de ômega 3 e 6 em animais de laboratório por via tópica (Rashid et al, 2008;Neves et al, 2013) e em humanos por via oral (Roncone et al, 2010;Pinheiro Jr. et al, 2007;Wojtowicz et al, 2011).…”
Section: Discussão E Conclusãounclassified
“…Outra forma de tratamento para a CCS, que vem se destacando em estudos recentes, é a utilização de ácidos graxos essenciais (AGE), ômega 3 (ω-3) e ômega 6 (ω-6), principalmente no tratamento de pacientes portadores de diversas formas de deficiência lacrimal, como na Síndrome de Sjögren humana, tanto em suplementação oral (Barabino et al, 2003;Mavragani et al, 2006;Pinheiro Jr. et al, 2007;Roncone et al, 2010;Wojtowicz et al, 2011), como em experimentos por via tópica em ratos (Rashid et al, 2008) e por via tópica e oral em coelhos (Neves et al, 2013). Os principais efeitos terapêuticos do ω-3 e ω-6 são imunomodulador e anti-inflamatório.…”
Section: Introductionunclassified